2019
DOI: 10.1039/c8cp07352j
|View full text |Cite
|
Sign up to set email alerts
|

The role of solvation models on the computed absorption and emission spectra: the case of fireflies oxyluciferin

Abstract: Absorption and emission energies calculation covering both implicit and explicit solvation models using oxyluciferin as the case of study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Vibrationally resolved absorption spectra have been computed on the basis of the TD‐DFT vibrational signatures by using the Franck‐Condon‐Herzberg‐Teller (FCHT) approximation and the Adiabatic Hessian method as implemented in Gaussian 16 . A comparison of the FranckCondon (FC) and FCHT vibrationally resolved absorption and emission spectra of oxyluciferin has been already discussed in a previous study, showing that the FCHT spectra resemble the FC ones. For this reason, only the FCHT spectra are simulated in this study.…”
Section: Methodsmentioning
confidence: 82%
“…Vibrationally resolved absorption spectra have been computed on the basis of the TD‐DFT vibrational signatures by using the Franck‐Condon‐Herzberg‐Teller (FCHT) approximation and the Adiabatic Hessian method as implemented in Gaussian 16 . A comparison of the FranckCondon (FC) and FCHT vibrationally resolved absorption and emission spectra of oxyluciferin has been already discussed in a previous study, showing that the FCHT spectra resemble the FC ones. For this reason, only the FCHT spectra are simulated in this study.…”
Section: Methodsmentioning
confidence: 82%
“…(As discussed in Section 5.2, the cLR formalism encountered in some of these studies is really a ptSS‐PCM approach, and typically outperforms true LR methods for excitations with charge‐transfer character.) Even for states that are not dominated by charge transfer, the SS‐PCM approach generally affords smaller errors for solvatochromatic shifts in the absorption spectrum as compared to LR‐PCM calculations, 586,597,631 although it is worth bearing in mind that the experimental λ max need not correspond to the origin (0–0) transition, due to vibrational structure 664–666 . The ptSS‐PCM approach also affords more accurate results for emission energies, 667 though it is found that the accuracy is largely unaffected if the LR‐PCM procedure is used for the excited‐state geometry optimization, followed by a ptSS‐PCM single‐point calculation, which simplifies the procedure 667 .…”
Section: Nonequilibrium Solvationmentioning
confidence: 99%
“…The nature of the emitter depends on the pH and the "local" pH inside the cavity is not an experimentally measurable. Joint experimental and computational studies of solvated emitters and of analogous systems in which the key reactions like the keto-enol tautomerization of the thiazolone moiety or the deprotonation of the phenolate group are blocked show that the experimental observations can be reproduced by protocols, which take into account dynamics of the protein, and that the use of analogues helps to better understand the nature of the light emitter (35)(36)(37). Nevertheless, accounting for fluctuating protonation states of the protein residues still needs to be improved.…”
Section: Challenges In Modeling Bioluminescent Systemsmentioning
confidence: 99%